THU0431 The Prediction and Benefits of Minimal Disease Activity in Patients with Psoriatic Arthritis in the Adept Trial. (9th June 2015) - Mease, P.; Kavanaugh, A.; Coates, L.; McInnes, I.; Hojnik, M.; Zhang, Y.; Anderson, J.; Dorr, A.; Gladman, D.
Abstract : Background: Minimal disease activity (MDA) 1 is a clinically meaningful and comprehensive treatment target for psoriatic arthritis (PsA). Objectives: To determine if baseline (BL) disease activity and/or patient (pt) demographics predict the ability to achieve MDA at week (wk) 12 in pts with PsA, and to evaluate patient-reported outcomes (PROs) at wk 24 associated with achieving MDA. Methods: Data were from the ADEPT (NCT00646386 ) trial of adalimumab vs placebo in pts with PsA. BL characteristics which predicted achievement of MDA at wk 12 were identified by univariate and multivariate (LASSO) analyses. Continuous variables were age, weight, modified total Sharp score (mTSS), tender/swollen joint count (T/SJC), Pt Global Assessment of disease activity (PtGA) or pain (PtGA-pain), Physician' s Global assessment of disease activity (PhGA), Health Assessment Questionnaire (HAQ), dactylitis, enthesitis (2 sites), Psoriasis Area Severity Index (PASI) and Physician's Global Assessment of Psoriasis (PGAP). Categorical variables were gender, smoking (yes/no), alcohol use (yes/no), methotrexate use (yes/no), rheumatoid factor status, presence/absence of investigator-reported spondylitis, C-reactive protein levels (<2.87 vs ≥2.87), duration of psoriasis/ PsA (<5 or ≥5 years). Pts achieving MDA or not at wk 24 were termed achievers and non-achievers (NA) respectively. PROs assessed at wk 24 were quality of life (QoL) by Dermatology Life Quality Index (DLQI) and Short Form 36 (SF-36) scores (total, physical/ mental component summary (P/MCS), and Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) score. Minimum clinically important differences (MCID) are: DLQI ≥5; SF-36 ≥5; M/PCS ≥2.5; FACIT-F ≥4. Results: In the univariate analysis, lower scores at BL for PtGA-pain, SJC66, TJC68, enthesitis and HAQ predicted MDA at wk 12. In the multivariate analysis, a one unit increase in BL HAQ and enthesitis score reduced the odds of achieving MDA at wk 12 by 37.6% and 16.0% respectively. The odds of achieving MDA was reduced by 22.6% for pts with spondylitis at BL compared to pts without spondylitis. At wk 24, MDA achievers (n=27) had significantly better scores (p<0.01) for all PROs than NA (n=98): total SF-36 score (65.3±13.4 vs 41.7±17.0), SF-36 PCS (51.0±7.2 vs. 35.0±10.8), SF-36 MCS (53.2±11.4 vs 45.9±10.7), FACIT-F (43.5±10.6 vs. 30.5±12.2), DLQI (2.1±5.4 vs 6.9±6.8). Achievers had favorable scores at BL already for SF-36 total, PCS and FACIT-F, but not for MCS and DLQI. Achievers had larger changes from BL than NA for all PROs, and reached MCID for all PROs; NA reached MCID only for SF-36 PCS. Age, gender, PsA duration and MTX use did not influence the PROs. Conclusions: Absence of spondylitis and lower scores for HAQ and enthesitis at BL were found to increase the likelihood of achieving MDA at wk 12. MDA achievement at wk 24 was associated with clinically important improvement in QoL and fatigue. References: Coates et al ARD, 2010; 69: 48-53. Acknowledgements: AbbVie funded the study and participated in design; data collection, analysis, and interpretation and in writing the publication. Medical writing support was provided by Naina Barretto, PhD, of AbbVie. Disclosure of Interest: P. Mease Grant/research support from: from AbbVie, Amgen, Biogen Idec, Bristol Myers, Celgene, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, and Vertex., Consultant for: from AbbVie, Amgen, Biogen Idec, Bristol Myers, Celgene, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, and Vertex., Speakers bureau: from AbbVie, Amgen, Biogen Idec, Bristol Myers, Celgene, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, and Vertex., A. Kavanaugh Grant/research support from: AbbVie Inc., Amgen, Astra-Zeneca, BMS, Celgene, Centocor-Janssen, Pfizer, Roche, and UCB., Consultant for: AbbVie Inc., Amgen, Astra-Zeneca, BMS, Celgene, Centocor-Janssen, Pfizer, Roche, and UCB., L. Coates Grant/research support from: AbbVie, Celgene, Janssen, Novartis, Pfizer and UCB., Consultant for: AbbVie, Celgene, Janssen, Novartis, Pfizer and UCB., Speakers bureau: AbbVie, Celgene, Janssen, Novartis, Pfizer and UCB., I. McInnes Grant/research support from: AbbVie, Amgen, Janssen, Novartis, Pfizer, and UCB., Consultant for: AbbVie, Amgen, Janssen, Novartis, Pfizer, and UCB., M. Hojnik Employee of: AbbVie Inc, Y. Zhang Employee of: AbbVie Inc, J. Anderson Employee of: AbbVie Inc, A. Dorr Employee of: AbbVie Inc, D. Gladman Grant/research support from: AbbVie, Amgen, BMS, Celgene, Eli Lilly, Janssen, Novartis, Pfizer, UCB., Consultant for: AbbVie, Amgen, BMS, Celgene, Eli Lilly, Janssen, Novartis, Pfizer, UCB.